The Role of Leadership in Team Sports: Fostering Entrepreneurship and Commitment in Sports Education - Sangpil Yoon; Minju Kim; Sanghyeok Park; Inbang Song (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study explores the influence of various leadership styles of sports leaders on entrepreneurship and organisational commitment among sports participants. It specifically investigates how these relationships differ based on the type of sport (individual versus group sports) and the age group (minors versus adults). The study used a quantitative research design and collected data from 400 participants involved in various sports activities in Korea via a cross-sectional survey method. To evaluate the variables, the study utilized the Leadership Scale for Sports (LSS) along with validated scales for entrepreneurship and organizational commitment. An analysis was conducted to examine the relationships and moderating effects of different sports and ages. The research reveals that behaviours associated with different leadership styles have a significant impact on entrepreneurship, with variations observed depending on the type of sport and age. Consistent predictors of organisational commitment were found to be social support, while the impact of positive feedback varied depending on the context. The training instruction's results did not have a significant impact on either outcome. In order to effectively promote entrepreneurship and organizational commitment, the study suggests customizing leadership in sports to suit the unique context and demographic. It highlights the significance of employing adaptive leadership strategies in sports education and management. These findings have practical applications for sports leaders who want to improve team performance and foster loyalty.